Introduction to Safe and Appropriate Cosmetics for Teenagers Vocational School - Honifa; Wulandari, Asri; Fatmi, Mindiya; Handayani, Marybet Tri Retno; Nurhikmah, Wilda (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2024)
Cosmetics are beauty products intended for use on the skin, hair, nails, lips, external genital organs, teeth, and oral mucosa. Knowledge about choosing the right cosmetics is necessary because many people make mistakes in determining the type of cosmetics to use, the types of ingredients used, and cosmetic rules. One step to increase awareness of safe ingredients and the use of cosmetics is to provide education through the university's education, research, and community service activities, namely Community Service. especially among teenagers. This activity aims to provide outreach on how to choose safe and appropriate cosmetics for teenagers and provide education on how to report side effects from using cosmetics to BPOM. In community service activities, the method used is to provide material using a lecture method, followed by discussion and questions and answers. Questions asked for pre and post-test are the same, namely the definition of cosmetics, the purpose of using cosmetics, how to store cosmetics, how to use cosmetics safely, how to choose to buy cosmetics from the marketplace, Knowing Dangerous Cosmetic Ingredients, Seeing Cosmetic ED, How to Store Cosmetics and regarding if you experience irritation/ side effects from cosmetic preparations, then the last order that was carried out after providing the material was that residents' knowledge increased when they filled out the same questionnaire again and was quite different compared to before. Like Knowledge of the meaning of cosmetics education who knew the meaning of cosmetics was 10 people or 45.4% after education increased to 19 people or 86.4% and for other questions there was an increase after providing the material. It can be said that the Community Service Activities that have been carried out can broaden the knowledge of teenagers.